Image of a eight-armed Chamunda in the Devakoshtha (niche) - Temples of India Project Team (Jio Institute, 2024)
Pictured here are the details of the bhadra (central projection) from the north-facing elevation of the Mahanaleshwar Temple. The devakoshtha (niche) on the central bhadra projection is a deep niche with an image of eight armed Chamunda inside. The devakoshtha is made up of two ornate pilasters that have icons at the base. These pilasters stand on a pedestal which is fashioned like a kapotali (cyma recta) and supports an udgama (pediment) above. This udgama is made up of a mesh of gavakshas (chaitya or dormer window arches) arranged like a pyramid. The east and west-facing sides of the devakoshthas have attendants. Chamunda has a skeletal body, stands on a dead human body, and holds a kapaal (human skull), khatvanga (staff with a skull), trishula (trident), naag (serpent), damru (hourglass-shaped drum), etc. attributes. She is biting the finger of her upper left hand.